Resistance and dissonance in higher education: On doing things differently - Davids, N.; Waghid, Y. (South African Journal of Higher Education, 2018)
The historical inequalities and imbalances, so deeply embedded in the institutional structures and discourse of higher education, continue to haunt university spaces as these institutions continue to veer along the precipice of transformation. While statues have been removed, buildings renamed, and fees adjusted, higher education in South Africa remains a largely disparate and alienating topography – no more so because of the gaping wounds left by iterative student protestations. Seemingly, the more leadership structures in higher education stonewalled student protestations, the more student resistance intensified – not only in scope, but in violence. In this sense, we are reminded of Foucault’s (1997) dyadic depiction of power and resistance – that is, that power necessarily provokes resistance, since without resistance, there can be no power. In this article, we reflect, on the necessity of resistance not only in relation to power, but as a practice that ought to be ubiquitous to higher education. And secondly, we argue that if higher education is to fulfil its ideological mandate of doing things differently for the sake of epistemological and public good, then it necessarily has to be underscored by dissonance.